ANALYSIS OF MANAGEMENT ACCOUNTING SYSTEM IMPLEMENTATION IN SUPPORTING THE COMPETITIVE ADVANTAGE OF THE AGRITECH KOPITANI.ID STARTUP - Arini; Agusdiwana Suarni; Khadijah Darwin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
This descriptive qualitative study investigates the implementation of a Management Accounting System (MAS) via the Paper.id digital platform at Kopitani.id, an agritech startup. The research aims to evaluate how digital accounting information supports strategic decision-making and fosters competitive advantage. Data were collected through interviews, observation, and documentation with the company's management. The findings indicate that Paper.id significantly enhances operational efficiency by streamlining receivable management, automating weekly inventory control, and providing organized financial reports compared to manual methods. These outputs allow management to maintain liquidity and optimize stock levels effectively. Although the study identified operational challenges, such as inconsistent data entry during 2024–2025 due to human resource limitations, the system remains a vital tool for the company. In conclusion, the integration of a digital MAS is crucial for creating the operational agility necessary to sustain a competitive edge in the dynamic agritech industry.